Feature of statistical data processing by computer mathematics systems tools - Moshchenko, I.; Nikitenko, O.; Kozlov, Yu.; Zharko , Yu. (Radiotekhnika, 2021)
Processes of error accumulation were analysed during arithmetic operations on statistical data obtained in the course of research on oscillations in cross-field electron vacuum devices. The features of statistical data processing obtained as a result of experimental research were investigated using the most widespread computer mathematical packages. The features of statistical data processing were investigated by processing a sample of 80 values of the magnetron generation frequency using popular mathematical packages Excel, Maple, Matlab and MathCad and comparing the results obtained with calculations using theoretical formulas. Calculation results for all packages give the same results for mean, variance and standard deviation. As for the coefficients of skewness and kurtosis, most of the results do not coincide. Analysis of the calculation results showed that the difference in the obtained values ​​of the skewness and kurtosis is due to different definitions of these indicators in mathematical packages Excel, Maple, Matlab and MathCad. It is proved that in Microsoft Excel we cannot correctly construct a histogram without using additional operations, because the interval limits are calculated with errors. It leads to an incorrect determination of the number of elements into these intervals. To build correctly a histogram using the Excel package, it is necessary to calculate the interval limits in advance. It is concluded that before using computer mathematical packages for processing statistical data, it is necessary to analyze first by what formulas the required parameters are calculated and take appropriate measures to eliminate possible discrepancies with the parameters calculated using theoretical formulas.